The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11547-017-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging for the cellularity assessment and matrix characterization of soft tissue tumour

Abstract: DWI may offer adjunctive information about soft tissue tumours, but its clinical role is still to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The contrast enhancement and increased K trans value indicated that the original tumors exhibited significant angiogenic activity and high vascular permeability (36), which may be attributed to the increased expression levels of the angiogenesis-associated genes in the original tumors (37)(38)(39). The rADC values of the original tumors were significantly lower compared with the xenografts, which may be attributed with the higher expression levels of the cell adhesion and extracellular matrix-associated genes noted in the original tumors, which in turn resulted in a higher cell density (40,41). Therefore, the differences noted in gene expression levels may underlie the differences noted in the MRI features between the original tumors and the corresponding xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast enhancement and increased K trans value indicated that the original tumors exhibited significant angiogenic activity and high vascular permeability (36), which may be attributed to the increased expression levels of the angiogenesis-associated genes in the original tumors (37)(38)(39). The rADC values of the original tumors were significantly lower compared with the xenografts, which may be attributed with the higher expression levels of the cell adhesion and extracellular matrix-associated genes noted in the original tumors, which in turn resulted in a higher cell density (40,41). Therefore, the differences noted in gene expression levels may underlie the differences noted in the MRI features between the original tumors and the corresponding xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…DWI in soft tissue tumors (STTs) is generally used with at least three b -values (from b = 50 to b = 1000) [ 103 , 104 ]. According to some authors, minimum ADC may be more accurate for characterization compared to mean ADC, while mean ADC should be preferred for tumor follow-up and treatment response evaluation [ 105 ].…”
Section: Soft Tissue Tumorsmentioning
confidence: 99%
“…To overcome this limitation, perfusion-insensitive ADC values can be used. Myxoid STTs show higher intrinsic diffusion coefficients due to their elevated mucin contents, and the difference in ADC between benign and malignant myxoid STTs was reported to be not statistically significant in some studies [ 103 , 104 ]. Similarly, both benign and malignant fatty STTs have very low ADC [ 106 ] ( Figure 13 A–D).…”
Section: Soft Tissue Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without recurrent haemorrhages and concentration of haemoglobin derivatives (deoxyhaemoglobin and methaemoglobin), viscosity of the cyst remains lower and shading sign is unlikely to be observed (17). Diffusion weighted imaging is a MR sequence which provides functional information by probing the random motion of water molecules in biological tissues, also with a quantitative assessment of diffusivity calculated on the ADC map (18)(19)(20)(21)(22)(23). Endometriomas tipically show low ADC values mainly due to "T2 blackout effects", related to the low T2-weigthed signal intensity of the lesions (24).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%